2017
DOI: 10.1016/j.jmoldx.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Validation of the Next-Generation Sequencing Assay for a Nationwide Signal-Finding Clinical Trial

Abstract: The National Cancer InstituteeMolecular Analysis for Therapy Choice (NCI-MATCH) trial is a national signal-finding precision medicine study that relies on genomic assays to screen and enroll patients with relapsed or refractory cancer after standard treatments. We report the analytical validation processes for the next-generation sequencing (NGS) assay that was tailored for regulatory compliant use in the trial. The Oncomine Cancer Panel assay and the Personal Genome Machine were used in four networked laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 19 publications
2
116
0
Order By: Relevance
“…This relatively high success rate was related to the standardised preanalytical and analytical procedures, including formalin fixation (10% neutral buffered formalin for 6–48 hours), case selection and automated analytical steps (ie, Ion Chef for the template preparation) 27. As a CE-IVD marked NGS assay, the Oncomine Solid Tumour kit enables multiplexed sequencing of FFPE tumour samples with the accuracy (overall sensitivity and specificity of 96.98% and 99.99%, respectively) required by a clinical diagnostic laboratory 28. Recently, the analytical sensitivity of this panel was further validated by a ring study that confirmed the sensitivity reported by the manufacturer 29.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively high success rate was related to the standardised preanalytical and analytical procedures, including formalin fixation (10% neutral buffered formalin for 6–48 hours), case selection and automated analytical steps (ie, Ion Chef for the template preparation) 27. As a CE-IVD marked NGS assay, the Oncomine Solid Tumour kit enables multiplexed sequencing of FFPE tumour samples with the accuracy (overall sensitivity and specificity of 96.98% and 99.99%, respectively) required by a clinical diagnostic laboratory 28. Recently, the analytical sensitivity of this panel was further validated by a ring study that confirmed the sensitivity reported by the manufacturer 29.…”
Section: Discussionmentioning
confidence: 99%
“…As the National Cancer Institute launched the NCI-MATCH trial 33–35 , an ongoing screening effort of 795 samples (according to the interim analysis at http://ecog-acrin.org/nci-match-eay131/interim-analysis) identified 9% mutations matching one of the 10 arms of the study. To a large extent influenced by the study drug/gene “menu”, finding the matched mutation was as likely as 18% in melanoma, brain tumors and lymphomas, 13% in colorectal and breast cancers vs. no matching in all screened so far patients with pancreatic adenocarcinoma, head and neck, endometrial, and small cell carcinoma.…”
Section: Rethinking the Clinical Trials Conductmentioning
confidence: 99%
“…The approach to analytic validation of the targeted NGS assay used in the NCI-MPACT trial was recently reported in this journal [7]. It is clear that findings from validation of the NCI-MPACT assay were helpful to Lih et al in their approach to the NCI-Molecular Analysis for Therapy Choice (MATCH) Trial which presented an even broader challenge for the laboratories [1]. …”
Section: Precision Medicine Enables “Genotype To Phenotype” Oncology mentioning
confidence: 99%
“…Although it is clear that assay validation is essential for clinical implementation, it could be questioned what each contributes to the literature. To place the study of Lih et al [1] in the appropriate context, some of the more recent validation studies with closest similarity to that of Lih et al will be reviewed.…”
Section: Overview Of Ngs Assay Validationmentioning
confidence: 99%
See 1 more Smart Citation